Study of Vernier permanent magnet machine with the dual rotor, toroidal winding and ferrite magnet on both sides of stator and rotor. Issue 13 (26th January 2021) - Yang, Yubo; Wang, Ying; Zhu, Changqing; Wang, Xiuhe; Zhang, Ran
Abstract : A dual‐rotor permanent magnet Vernier machine (DRPMVM) with permanent magnets (PMs) on both sides of the rotor and stator is proposed and studied here. The configuration and working principle are provided, then the expression of coil‐side voltage is obtained based on the rotating harmonics of the air gap flux density. The effects of the rotor slot number on the amplitudes and phase differences of the voltage components are explored, and suitable combinations of the stator and rotor slot numbers are selected. The impact of the rotor and stator PMs on the voltage is also compared. Different coil connection methods are adopted for the DRPMVM with 12‐stator slot and 10‐rotor slot, and the back electromotive force, d ‐ and q ‐axes inductances, and torque‐speed characteristics are compared. Using the finite element method, the effect of the main parameters, including slot and yoke width on the average torque and torque ripple are then studied. Finally, a prototype machine is produced and tested to verify the conclusions.